The Relationship between the Investor’s Sentiment and Vietnam Stock Market - Nguyen Thu , Hoai; Dang Phong , Nguyen; Dang Thi Viet , Duc; Nguyen Thanh , Huyen (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The study analyzes the relationship between investor emotion and the volatility of Vietnam's stock market. Using data for the period 2018–2023 and employing a standard VAR model, the results show that there is an interrelationship between the volatility of the Vietnamese stock market and investor sentiment. The impact of changes in the market on investor emotion is quite large, more than 10%. Meanwhile, investor emotion also has an effect on market volatility, about 25%. The level of impact gradually decreased over time after 3 periods (weeks) in the study. This result suggests that investors' emotions are a reliable source for references in technical analysis and volatility assessment of Vietnam's stock market.
Keywords: Investor sentiment; Stock market; Stock return